Impaired antiviral activity of interferon alpha against hepatitis C virus 2a in Huh-7 cells with a defective Jak-Stat pathway - Kousoulas Gus (Virology Journal, 2010)
Abstract Background The sustained virological response to interferon-alpha (IFN-α) in individuals infected with hepatitis C virus (HCV) genotype 1 is only 50%, but is about 80% in patients infected with genotype 2-6 viruses. The molecular mechanisms explaining the differences in IFN-α responsiveness between HCV 1 and other genotypes have not been elucidated. Results Virus and host cellular factors contributing to IFN responsiveness were analyzed using a green fluorescence protein (GFP) based replication system of HCV 2a and Huh-7 cell clones that either possesses or lack a functional Jak-Stat pathway. The GFP gene was inserted into the C-terminal non-structural protein 5A of HCV 2a full-length and sub-genomic clones. Both HCV clones replicated to a high level in Huh-7 cells and could be visualized by either fluorescence microscopy or flow cytometric analysis. Huh-7 cells transfected with the GFP tagged HCV 2a genome produced infectious virus particles and the replication of fluorescence virus particles was demonstrated in naïve Huh-7.5 cells after infection. IFN-α effectively inhibited the replication of full-length as well as sub-genomic HCV 2a clones in Huh-7 cells with a functional Jak-Stat pathway. However, the antiviral effect of IFN-α against HCV 2a virus was not observed in Huh-7 cell clones with a defect in Jak-Stat signaling. HCV infection or replication did not alter IFN-α induced Stat phosphorylation or ISRE promoter-luciferase activity in both the sensitive and resistant Huh-7 cell clones. Conclusions The cellular Jak-Stat pathway is critical for a successful IFN-α antiviral response against HCV 2a. HCV infection or replication did not alter signaling by the Jak-Stat pathway. GFP labeled JFH1 2a replicon based stable cell lines with IFN sensitive and IFN resistant phenotypes can be used to develop new strategies to overcome IFN-resistance against hepatitis C.